Dynamic behavior of a power re-circulating gear test rig including periodic variation of mesh stiffness and static transmission error. (May 2021) - Abruzzo, M.; Beghini, M.; Santus, C.; Manconi, S.
Highlights: A gear test rig was discretized using a pure torsional lumped parameter model. The dynamic parameters of the system were calculated using a finite element model. The resonance frequencies of the rig were obtained using a traditional method. The dynamic response was calculated using an iterative integration algorithm. The results obtained were compared with the experimental ones. Abstract: We characterized the dynamic behavior of a pair of high performance aeronautical gears which are part of a complex transmission system. The gear pair was tested using a mechanical recirculating power test rig designed to simulate the severe operating conditions of transmitted torque and angular speed. The test rig and the most important phenomena that influence its dynamic behavior are described. A (static) finite element model, developed to calculate the input parameters for the dynamic analysis of the tested gears, is also presented. Using the results of the FE model, we developed a lumped dynamical model with which it is possible to reproduce the most significant dynamic phenomena of the test rig. We characterized the behavior of the test rig focusing on the actual loads transmitted by the tested gears. The dynamic model was validated by comparing its results with the experimental outcomes in various test conditions. The comparison highlights the limitations of the design procedures based on common standards for assessing the dynamic overload experienced by heavy-duty gear transmission systems.